CREATIVE PROCESS OF HALANG DANCE - Yulianti, Ninik Putri; Soemaryatmi, Soemaryatmi (ISI Press Institut Seni Indonesia Surakarta, 2022)
Halang dance is a choreographic work that departs from a folk tale, namely the love story of Raden Inu Kertapati with Galuh Candra Kirana who faces many obstacles. The formulation of the research problem, namely: How is the creative process of creating Halang dance? This study uses a practice-based research methodology. The creative process in creating this dance uses the 3R theory. The result shows that the artistic process gives freedom of interpretation and creativity to anyone to realize ideas in the form of works. Halang dance is a work of art that is done through a creative process by going through the steps of Re-Visiting, Re-Questioning, and Re-Interpreting. Then through the steps of the creation process, namely exploration, improvisation, composition, evaluation, rehearsal, and performing. Halang dance is performed by four scenes as a literal dramatic choreography. The elements in Halang dance are able to convey the atmosphere and message to the audience that in truth life will never be separated from all problems and love will continue to grow and develop in souls who have sincerity.